Effect of Parenteral Corticosteroids in Mortality from Severe Covid-19 - Meregildo-Rodriguez, Edinson Dante (2021)
Introduction. Infections caused by SARS-CoV-2 may produce a severe inflammatory response, sepsis, respiratory failure, organ dysfunction, and death. From a pathophysiological point of view, it is plausible that glucocorticoids could be a reasonable therapeutic option for Covid-19. However, the evidence supporting the benefit of corticosteroids on mortality and other clinical outcomes is not conclusive. Objective: determinate if there exist evidence supporting corticosteroids therapy in patients with severe Covid-19 and Acute Respiratory Distress Syndrome (ARDS). Material and method: This study was performed in concordance with PRISMA guidelines. According to the PICO strategy, Population were patients with severe Covid-19 and/or ARDS; Intervention, parenteral corticosteroid administration; Comparator, patients with severe Covid-19 and/or ARDS with standard treatment (without corticosteroids); and Outcome, mortality and other clinical outcomes. Search strategy was performed in the data bases PubMed, Medline, Cochrane, Embase, and LILACS, using terms related with the PICO question; from January 1 to august 31 (2020). A total of 287 articles were initially retrieved. Of these, we finally selected only 9 article which fulfilled with PICO and selection criteria. Results: According to our study, parenteral corticosteroids reduce mortality in patients with Severe Covid-19 and/or ARDS [OR 0.83 (IC 95% 0.63-1.08)]. Conclusion: the systematic review shows that parenteral corticosteroids could reduce the mortality of patients with severe Covid-19 and ARDS.